ANALISIS KEPATUHAN PEKERJA TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PROYEK PESONA SQUARE SOUTH SIDE APARTMENT (SSA) KOTA DEPOK TAHUN 2020 - Desty Safitri (2021)
Compliance with the use of PPE is now one of the significant causes of work accidents. The majority of work accidents at the SSA Pesona Square Project are caused by the human factors that do not use PPE while working. The aim of this study was to analyze worker compliance through age, education, working period, knowledge, attitude, training, and supervision of the use of PPE in the SSA Pesona Square Project. This research was used quantitative analytic research with cross-sectional design. The sample of this study was all 100 SSA Pesona Square Project workers with the determination of inclusion and exclusion criteria to 88 workers. The results showed that 56.8% of workers uncomply in using PPE. Statistical analysis results showed knowledge (P-value = 0.001), attitude (P-value = 0.040), training (P-value = 0.007), and supervision (P-value = 0.023) had a significant relationship with compliance with the use of PPE. While age (P-value = 0.439), education (P-value = 0.373), and working period (P-value = 0.187) did not have a significant relationship with compliance the use of PPE. Therefore, the company is advised to improve the knowledge and attitude of workers administratively and carry out training and supervision routinely so that project workers comply using PPE.